Self-administration of Recombinant Human Growth Hormone with an Electronic Device: Clinical, Economic and Management Benefits of Objective Adherence Monitoring - Zuleika Saz-Parkinson; Maria Del Sol Granados Alonso; Carmen Bouza; José Luis Poveda Andrés; José María Amate (Journal of Health Economics and Outcomes Research)
**Purpose:** The aim was to identify factors affecting treatment adherence and to assess the clinical, economic and management impact of growth hormone deficiency treatment using an electronic auto-injector for recombinant human growth hormone (r-hGH) administration in children.